PENDAMPINGAN TKA BAGI SISWA SMAN 2 KOTA SOLOK UNTUK MENINGKATKAN PRESTASI AKADEMIK - Helvita Roza; Ratih Komala Dewi; Darmanella Dian Eka Wati; Chairul Amri; Afrahamiryano Afrahamiryano; Irwan Hanafi (ASOSIASI IDEBAHASA KEPRI, 2026)
Scientific literacy encompasses not only the ability to understand scientific concepts but also the capacity to connect science to everyday life and apply that knowledge to problem-solving. Preliminary observations at SMAN 2 Solok City revealed that students' scientific literacy levels remain low. This issue contributes to weak critical and analytical thinking skills, as well as insufficient readiness for advanced studies or academic competitions. To address this challenge, the community service team proposes an integrated biology outreach program designed to enhance students' scientific literacy. The program employs a contextual approach by presenting real-world problems relevant to the students' daily lives. Activities are structured as interactive discussions that combine biological concepts with mathematical analysis. The intended outcomes of this initiative are: (1) improved scientific literacy among SMAN 2 Solok City students, and (2) publication and documentation of the activities. Through this program, it is expected that students will become more proficient in integrating scientific knowledge, develop critical thinking skills, and achieve a higher level of scientific literacy. Keywords: Scientific Literacy, Integrated Outreach, Biology.